THE RELATIONSHIP BETWEEN LEARNERS’ AUTONOMY AND THEIR ACHIEVEMENT IN LEARNING ENGLISH AT 11TH GRADE OF SMA NEGERI 1 TEMBILAHAN HULU - M. Tomy; Edi Ardian; Agus Mustajib (J-Shelves of Indragiri (JSI), 2020)
The problem of this research was Learners' achievement seems low, while their autonomy seems higher. The method of this research was quantitative correlation research. Therefore, the purpose of this study was to investigate the correlation between learners' autonomy (Variable X) with learners' achievement (Variable Y). The sample of this study was 145 students of eleventh-grade students of SMAN 1 Tembilahan Hulu. The researcher gave questionnaires of learners' autonomy to collect data and asked the value of their English teacher's achievement. After the data has been collected, it was found that the average of learners' autonomy is 77,9%, it was in the "high category," And the average of learners' achievement was 81,6%, it was in the "high category". Based ." those findings, researchers analyzed the relationship between learners' autonomy and their achievement using the Pearson r formula; the results was 0.1999 (rxy) it was in "very low correlation," after found out the score of rxy researcher noting to the table of degree of freedom (df) N (number of respondents) – nr (variables) where 145 – 2 is 143. By consulting r table product-moment, it is found in the significant of 1% being obtained at 0.1371 and 5% is 0.1631. By comparing the values of rxy = 0.1999 and r table = 0.1371 and 0.1631, rxy is bigger than r table. This means that autonomy and achievement have a very low correlation. If learners have good autonomy, they will have a good achievement in English.